2022
DOI: 10.1055/s-0042-1759614
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Pipeline in Alcohol-Associated Liver Disease

Abstract: Alcohol-associated liver disease is a leading cause of mortality and morbidity worldwide. Patients with alcohol-associated liver disease are often diagnosed at advanced stage and disease spectrum including alcoholic hepatitis, a severe manifestation with a high short-term mortality. Corticosteroid, recommended first-line treatment for patients with alcoholic hepatitis, is a very suboptimal treatment. Although the use of early liver transplantation has increased with consistent benefit in select patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 126 publications
0
5
0
1
Order By: Relevance
“…Despite alcohol-related disorders' high prevalence and negative impact, treatment rates among individuals reported to have harmful alcohol consumption are estimated to be below 5%. 22 Increased awareness and education on all levels, including health care providers, social workers, and patients, and counselling services must be estab- with end-stage liver disease. 16 Similarly, several studies from Europe and Australia confirmed a remarkable reduction in in-hospital mortality among patients with cirrhosis before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite alcohol-related disorders' high prevalence and negative impact, treatment rates among individuals reported to have harmful alcohol consumption are estimated to be below 5%. 22 Increased awareness and education on all levels, including health care providers, social workers, and patients, and counselling services must be estab- with end-stage liver disease. 16 Similarly, several studies from Europe and Australia confirmed a remarkable reduction in in-hospital mortality among patients with cirrhosis before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a steady increment in the burden, morbidity and mortality of ALD‐related cirrhosis during the COVID‐19 pandemic. Despite alcohol‐related disorders' high prevalence and negative impact, treatment rates among individuals reported to have harmful alcohol consumption are estimated to be below 5% 22 . Increased awareness and education on all levels, including health care providers, social workers, and patients, and counselling services must be established.…”
Section: Discussionmentioning
confidence: 99%
“…proteomic, transcriptomic, epigenomic, metabolomic, and single‐cell sequencing technologies) have yielded deeper insights into the pathogenesis of AH. This could be of great relevance for the development of new targeted treatment approaches and personalized management 7,10,11,25,58 …”
Section: Current Management Approaches Of Ahmentioning
confidence: 99%
“…The mortality rate for patients with moderate AH (MELD 11-20) ranges from 3 to 10% within 3 months from presentation and may increase up to 20% at one year. 7,58 The mortality of patients with severe AH who do not respond to medical treatment is estimated to be 30%-40% at 1-month and can increase up to a 6-month mortality of 70% without transplantation. 11 The long-term prognosis of AH is primarily determined by the occurrence of alcohol relapse.…”
Section: Prognosismentioning
confidence: 99%
“…Еще более сложным вопросом является определение показаний к применению гепатопротекторов, выбор конкретного препарата, схемы и продолжительности лечения [4,5]. На фармацевтическом рынке представлено большое количество гепатопротекторов с разными составом, тропностью к печени и механизмами действия.…”
Section: Introductionunclassified